Cardiovascular surrogate markers and cardiometabolic therapeutics: a viewpoint learned from clinical trials on dipeptidyl peptidase-4 inhibitors - Atsushi Tanaka (Cardiovascular Diabetology, 2021)
Abstract Clinical trials are often performed to investigate the effects of various types of cardiometabolic therapies on cardiovascular surrogate markers, including vascular function and biomarkers. This study platform has the potential to provide information on the suspected actions of drugs and mechanistic insights into their prognostic impact. However, despite using the same class of drugs and similar study designs we are often faced with inconsistent and even conflicting results, possibly leading to some confusion in the clinical setting. When interpreting these results, it is important to investigate what caused the differences and carefully assess the information, taking into account the research situation and the patient population investigated. Using this approach, assessment of the impact on cardiovascular surrogate markers observed in clinical studies from multiple perspectives should help to better understand the potential cardiovascular effects. In this commentary we discuss how we should interpret the effects of cardiometabolic therapeutics on vascular surrogate markers, based on viewpoints learned from the results of clinical trials on dipeptidyl peptidase-4 inhibitors. This learning strategy could also be helpful for appropriate selection of drugs for evidence-based, patient-centric, tailored medication.